IBADAH RITUAL DALAM MENANAMKAN AKHLAK REMAJA - Kastolani Kastolani (IAIN Salatiga, 2016)
This article explained what was viewed as ritual worship; pray and fasting to embed noble character. The purpose of worship in Islam are: (a) to strengthen belief and dedication to Allah; (b) to strengthen character, disciplining personality and his role as the agent trusted by Allah on earth; (c) to strengthen friend ship and affection among Muslim; (d) to train spiritual and moral. Character occupies crucial role in human’s life, as individual as well as society member. It is because the fall and raise of the nation depends on how its society character. The whole of worship system in Islam has close relation with character founding and the performance of ritual worship influences noble character, because good worship performance without having noble character will not useful. Abstrak Artikel ini menjelaskan apa yang dimaksud dengan ibadah ritual yaitu shalat dan puasa dalam menanamkan akhlak mulia. Tujuan ibadah dalam Islam yaitu: (a) Memperkuat keyakinan dan pengabdian kepada Allah. (b) Menguatkan karakter, mendisiplinkan diri dan peranannya sebagai wakil dan hamba yang dipercaya Allah di bumi. (c) Memperkuat tali persaudaraan dan kasih sayang diantara sesama muslim (d) Latihan spiritual dan moral. Kedudukan akhlak dalam kehidupan manusia menempati tempat yang sangat penting sekali, baik sebagai individu maupun sebagai anggota masyarakat. Sebab jatuh bangunya suatu bangsa akan tergantung pada bagaimana akhlak warganya. Seluruh sistem peribadatan dalam Islam mempunyai hubungan yang erat dengan pembinaan akhlak dan pelaksanaan ibadah ritual berpengaruh terhadap akhlak karimah, karena ibadah yang baik tanpa akhlak yang mulia ibadah itu tidak akan berguna